Blended learning in a first-year language class: Evaluating the acceptance of an interactive learning environment. - Olivier, Jako (Literator, 2016)
Increasingly blended learning, as a combination of face-to-face and online instruction is applied in university classrooms. In this study the use of an interactive learning environment (ILE), within a Sakai-based learning management system, as well as face-to-face teaching and learning in a first-year Afrikaans language class is explored. The Technology Acceptance Model (TAM) was employed by means of a survey and the Structure Equation Model was used to explore factors relevant to this first-year class. In addition, qualitative research was conducted through an open questionnaire in order to determine the perceptions regarding the blended learning context and the ILE. It was found that students are generally able to function within the ILE and they are quite positive towards the use of the learning environment for learning and teaching. However, it is clear that some students still prefer printed study material. Despite the fact that students indicated that they use the ILE daily, actual usage statistics did not always correspond. Finally, this paper makes suggestions with regard to adapting teaching in terms of students' behaviour based on their computer anxiety and Internet self-efficacy as well as the perceived usefulness and ease of use of the ILE.